Tata Kelola Perusahaan dan Manajemen Laba Riil pada Perusahaan Manufaktur di Bursa Efek Indonesia (BEI) - Mardianto Mardianto; Maria Trisnawati (Studi Akuntansi dan Keuangan Indonesia, 2022)
This study aims to examine the effect of the characteristics of the board of directors and audit committee on real earnings management. Three measurements are used to measure real earnings management, namely abnormal cash flow from operations, abnormal discretionary expenses, and abnormal production costs. Company management can manipulate operational activities such as sales, reduce discretionary costs and manipulate production levels excessively. The object under study is the annual reports of manufacturing companies from 2017 to 2021 which are listed on the Indonesia Stock Exchange. The data collected will be processed with the help of Eviews software. The data analysis method used is descriptive statistical analysis, panel data regression test, and hypothesis testing. The results of this study prove that the audit committee size variable has a significant positive effect on real earnings management, while the board of directors size variable, board of directors independence, board of directors meetings, audit committee independence, audit committee meetings, and audit committee expertise do not affect real earnings management.